Altruism Begets Altruism - Stephanie A. Heger; Robert Slonim (Center for Economic Studies and ifo Institute (CESifo), 2022)
Guided by Bem's (1972) self-perception theory, we design an experiment to ask whether morally-motivated behaviour, e.g., charitable giving, is history-dependent. Using a popular policy nudge, the default option, we exogenously vary altruism "now" and show that giving "now" causes a 66%- 200% increase in the probability of giving "later"; that is, altruism begets altruism. We further show that, consistent with self-perception theory, the choice to behave altruistically "now", rather than the nudge itself, is the crucial element in the causal relationship. These findings are consistent with a model of positive path-dependence, which we interpret as moral consistency.
Keywords: 330; altruism; nudge; moral consistency